The institutionalization of sustainability topic in the business administration course - Indiara Beltrame; Luciano Gomes dos Reis; Karina Rocha Henriques Gehlen (Revista Gestão Universitária na América Latina, 2018)
The objective of this work is to analyze how the Londrina State University Business Administration Undergraduate Course carried out the process of the institutionalization topic of sustainability.  To meet this goal the analysis was based on the theory of Tolbert and Zucker (1999) which subdivides the institutionalization process into three phases: habitualization, objectivation and sedimentation.  As for the methodology, this research is characterized as qualitative, with descriptive objectives, and case study.  Analysis of the legal and institutional documents related to the creation of a Business Administration course  in order to identify convergence points to include the sustainability theme showed that the course complies with the all legal norms and that the sustainability theme is already included in its pedagogical proposal (PPC). In what is relevant to the examination of the institutionalization process,pointed out to the following perspectives:  the sustainability process is pre-institutionalized in the Business Administration courses; the option for the institutionalization theme at the Londrina State University Business Administration course was mentioned as being the result of natural and spontaneous social demands motivated by  the search for a wider business administrator’s educational process, materialized  in the proposal for a curriculum that contemplates the sustainability as a transversal theme.